Fundamentals of financial management - Van Horne, James C.; Wachowicz, John Martin (Eaglewood Cliffs, N.J. : Prentice Hall, 1998)
The book introduces the reader to the three major decision-making areas in Financial Management: the investment, financing and asset management decision.
Includes one calculator guide for financial management.
Includes bibliographical references and index.
uaj 24/05/2015
Loan
Keywords: Corporations -- Finance; Business enterprises -- Finance